Forced migration, human rights and security - McAdam, Jane , 1974- (Oxford : HART Publishing, 2008)
This book responds to the contemporary challenges faced by the international protection regime, in particular the human rights of those displaced
1. Forced migration: refugees, rights and security -- 2. Resolution 1373: a call to pre-empt Asylum Seekers' (or 'Osama, the Asylum Seeker?) -- 3. National security and 'non-refoulement' in New Zealand: commentary on 'Zaoui v Attorney-General (No 2)' -- 4. Offshore barriers to Asylum Seeker movement: the exercise of power without responsibility? -- 5. The legal and ethical implications of extraterritorial processing of Asylum Seekers: the 'safe third country' concept -- 6. Re-thinking the paradigms of protection: children as convention refugees in Australia -- 7. Wearing thin: restrictions on Islamic headscarves and other religious symbols -- 8. Subjectivity and refugee fact-finding -- 9. Towards convergence in the interpretation of the refugee convention: a proposal for the establishment of an international judicial commission for refugees -- 10. The refugee convention as a rights blueprint for persons in need of international protection -- 11. The responsibility to protect: closing the gaps in the international protection regime
Includes bibliographical references and index
Keywords: Forced migration; Human rights; Refugees -- Legal status, laws, etc